PENGARUH INVESTASI SEKTOR PRIMER, INVESTASI SEKTOR SEKUNDER DAN INVESTASI SEKTOR TERSIER TERHADAP KESEMPATAN KERJA DI INDONESIA - Kevin Tri Saputra; Syamsul Amar; Ariusni Ariusni (Universitas Negeri Padang, 2018)
The purpose of this study is to analyze the effect of primary sector investment, secondary sector investment and tertiary sector investment on employment opportunities in Indonesia. The results of the research indicate that (1) primary sector investment has not positive effect on employment opportunity (2) secondary sector investment has positive effect on job opportunity in Indonesia work (3) tertiary sector investment has positive effect on employment in Indonesia. Based on the results of research suggested to the policy makers should make a policy or work program so that not all activities are carried out by technology and machinery of course by looking at other aspects so that can be reconsidered by the business. The government should also pay more attention to investment activities both Foreign Direct Investment and Domestic Investment.